The argumentative function of the character of Demosthenes in Aristophanes’ Knights (Circe de clásicos y modernos, 2018)
This paper aims to demonstrate that the character of Demosthenes plays a central role in the persuasive strategy of the piece, which attempts to degrade the public image of Cleon. In the early works, the comic hero is usually the main spokesperson who defends the position maintained in the work; however, the image of the hero in Knights, the Sausage-Seller, is so devaluated at first that the argumentative force of the attack becomes weak; in this sense, Demosthenes acts as a provisional hero and authorized spokesman for the enunciator-author until the Sausage-Seller reaches more legitimacy and true heroic stature.
Keywords: Demosthenes; Cleon; persuasive strategy; comic hero; legitimacy